Practices, Attitudes and Knowledge of COVID-19 among the University Students of LCWU, Lahore: Knowledge, Practices and Attributes of COVID-19 - Sharif, Saima; Ditta, Naila Allah; Naz, Shagufta; Manzoor, Farkhanda (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
The primary goal of this study was to analyze COVID-19-related knowledge, attitudes, and practices among Lahore College for Women University students (LCWU). Methods: A cross-sectional study was carried out among LCWU students. Data was collected using a self-administered questionnaire and processed using a Google Form. The data was analyzed statistically. Results: The total number of responses received was 114. According to our research, 98 percent of respondents were familiar with COVID-19, with 51.8 percent receiving information via social media. 68.4 percent thought the virus was contagious, 95.60 percent thought it was spread by respiratory droplets, and 24.8 percent thought the elderly and children were at risk. 93.9 percent of participants were aware of social/physical distancing and believed that it could help to prevent infection, 95.5 percent believed that cough and fever could be signs and symptoms of COVID-19, and 106 (93 percent) claimed that staying at home could help to prevent the disease from spreading. Conclusion: It was observed that the majority of individuals were aware of COVID-19, with 90% of the population knowing about it. There is an ever-increasing need for COVID-19 knowledge among the local populace. It will assist in the prevention of COVID-19 transfer with minimal secondary transmission. Extensive survey studies are needed to offer supporting evidence in the development and implementation of public health policies related to the COVID-19 pandemic. It would help to regulate and stop the spread of COVID-19 across the country.